Leksikon Flora dan Fauna dalam Peribahasa Nias: Kajian Ekolinguistik - Agus Darma Yoga Pratama; Alexsander Loi (Humanitatis : Journal of Language and Literature, 2023)
Nias proverbs are a form of communication used by Nias people in conveying feelings, ideas and ideas. Nias people use natural lexicons both biotic and abiotic in Nias proverbs. The relationship between language users and other language users as well as the relationship between language users and the social environment can be seen using the Band and Door dialogue method (1993).This research aimed to identify flora and fauna lexicons in Nias proverbs. The method used in this research was a quantitative method with a quantitative descriptive approach. The source of data in this research were primary and secondary data. The data collection technique used the interview method by applying the free listening method involved being proficient with note-taking techniques. Based on the results of the research, there were lexicons of flora and fauna: gae 'banana', silimo 'kecombrang', dima 'orange', tugala 'broken bone', dawuo 'betel', banio 'coconut', dὂwu 'sugar cane', dalimbo 'oyster mushroom'. ', landöta 'matsutake', mbulu nakhe 'palm leaf', bago 'tobacco', wakhe ' paddy', mbulu mbala 'papaya leaf', and ladari 'pandan leaf, manu 'chicken', mbawi 'pig', mbaewa 'eel ', nasu 'dog', baya komo 'lizard', mba'e 'monkey', mböhö 'deer', laosi 'Mouse Deer', nazese 'bird tledekan', siliwi 'sparrow', mbae'a 'snail', mbo'ole 'turtle', moyo 'eagle', and garawi 'weasel'. The use of the lexicon of flora and fauna in the formation of Nias proverbs has a function as subject and complement.